Energy security : pre-empting the next oil crisis. - Chan, Yong Han. (2008)
A second major oil crisis has the possibility of escalating into an armed conflict pitting global powers against each other. Discussion of the conduct of international political economy and strategic thought in a time of rising oil prices and supply disruptions.